Health Education for the Elderly to Prevent Depression Problems During a Pandemic Through Android Application - Pradana, Anung Ahadi; Sahar, Junaiti; Permatasari, Henny (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The COVID-19 pandemic condition causes the elderly to experience depression. Elderly access to health services during a pandemic requires health professionals to consider the use of an Android application as a method of approach. The method used in this paper is a case study with the aggregate of the elderly in Depok City. The sampling technique chosen was convenience sampling with a sample size of 38 people. The implementation of empowerment for the elderly is carried out using an android application named “Sadar Depresi Lansia”. The paired t-test results show that the use of android applications has a positive effect on the elderly’s understanding of depression (sig. = 0.000) and depression level in the elderly (sig. = 0.000). The use of innovative android applications to provide education and screening services to the elderly with depression can be one of the methods that can be used by health workers.